Reward Priority of Visual Target Singletons Modulates Event-Related Potential Signatures of Attentional Selection - Kiss, Monika; Driver, Jon; Eimer, Martin (Psychological Science, 2009)
We examined visual search for color singleton targets, whose shape was discriminated. Critically, we varied the reward priority of singleton colors (correct fast performance was worth more bonus points for red singletons than for green singletons, or vice versa) to test whether event-related potential signatures of visual selection can be affected by distinct reward priorities for different target types, even when every target has to be selected for report. The N2pc component was earlier and larger for high- than for low-reward targets. This influence of reward on the N2pc correlated with the subject-by-subject impact of reward level on efficiency of behavioral performance. Later postselection processing was also affected by reward level. These results demonstrate that visual selection of task-relevant items is rapidly modulated by reward-related priorities, even when every target has to be selected for response.